Mineral Fertilization with UAN on Natural Grassland Festuca rubra L. with Agrostis capillaries L. - Ioan Rotar; Mirela Cirebea; Roxana Vidican; Florin Păcurar; Anamaria Mălinaş; Ovidiu Ranta (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Agriculture, 2016)
An important part of efficient livestock production is ensuring the sufficient grass for hay and pasture. However, low soil nutrient levels often limit forage production. With good fertilizer management and soil fertility, the productivity of many hay and pasture fields can be greatly improved. Through good fertilizer management, the productivity of many hay and pasture fields can be significantly improved by Ross H. McKenzie (2005). The aim of this paper was the effect of fertilization with liquid fertilizer (UAN) the harvest of dry and floristic composition changing on natural grassland. The experiment whose results we present was placed in 2014 in the place in Baisoara Mountain village, Cluj County. Experience has been placed on the Festuca rubra and Agrostis capillaries - of grassland type. The natural grassland of Festuca rubra with Agrostis capillaries responded very well to mineral fertilizers with liquid fertilizer UAN. The floristic composition of natural grassland fertilized with liquid fertilizers based on nitrogen, it can be seen an increase the Gramineae families and an evidence downward trend from Fabaceae families.